A RARE CASE OF CO-EXISTENCE PITUITARY MACROADENOMA WITH MAYER-ROKITANSKY-KUSTER-HAUSER (MRKH) SYNDROME - Z, Nur Aisyah; AR, Rohaya; MS, Fatimah Zaherah; Y, Yusniza; AG, Rohan (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome or Müllerian agenesis is a congenital failure of the Müllerian duct to develop, resulting in complete or partial absence of the cervix, uterus, and vagina. It can be isolated (MRKH type I) or associated with renal, vertebral, auditory and cardiac defects (MRKH type II). It is not known that pituitary disease has any association with this condition. We report a patient who has MRKH type I and a pituitary macroadenoma, diagnosed concomitantly. CASE A 17-year-old lady was referred with primary amenorrhoea, occasional headache, nausea and lethargy. She denies any reduction or loss of vision. On clinical assessment, she had normal secondary female sexual characteristics, with Tanner stage 3. There was no significant family history. Hormonal investigations showed high prolactin level; 4200 miU/L (post dilutional). Estradiol was low, 37 pmol/l (93–1400 pmol/l), as well as FSH 2.38 U/L, LH 0.96 U/L, progesterone <0.3 nmol/L and testosterone <0.45nmol/L. Cortisol level 206 nmol/L, FT4 7.5 pmol/L with TSH 5.091 mIU/L. MRI of pituitary showed 2.7 cm (AP) x 3.7 cm (W) x 4.6 cm (CC) pituitary macroadenoma, with mass effect, infiltration into left cavernous sinus and encasement of cavernous portion of left ICA. MRI pelvis showed absent uterus, cervix and 2/3 upper vagina confirming Müllerian hypoplasia. Cytogenetics showed 46XX. Diagnosis of Mayer Rokitansky Kauser Hauser Syndrome and panhypopituitarism secondary to pituitary macroadenoma was made. She was treated with hydrocortisone, levothyroxine and cabergoline. Follow up MRI has shown reduction in tumour size. However, she has remained amenorrhoeic. CONCLUSION The estimated prevalence of MRKH syndrome is one in 4500 female births. The etiology of MRKH syndrome remains unclear. There is no known association with pituitary disease. To the best of our knowledge this is the first case of co-existing MRKH syndrome and pituitary adenoma reported from the ASEAN world.